Susceptibility of Influenza Viruses to the Novel Cap-Dependent Endonuclease Inhibitor Baloxavir Marboxil - Takashita, Emi; Morita, Hiroko; Ogawa, Rie; Nakamura, Kazuya; Fujisaki, Seiichiro; Shirakura, Masayuki; Kuwahara, Tomoko; Kishida, Noriko; Watanabe, Shinji; Odagiri, Takato (Frontiers in Microbiology, 2018)
The novel cap-dependent endonuclease inhibitor baloxavir marboxil was approved for the treatment of influenza A and B virus infections in February 2018 in Japan. Because of the need to monitor influenza viruses for reduced susceptibility to this drug, we used two cell-based screening systems––a conventional plaque reduction assay and a focus reduction assay––to evaluate the susceptibility of influenza viruses to baloxavir. First, we generated a reference virus possessing an I38T substitution in the polymerase acidic subunit (PA), which is known to be associated with reduced susceptibility to baloxavir, and demonstrated the validity of our systems using this reference virus. We then determined the susceptibility of a panel of neuraminidase (NA) inhibitor-resistant viruses and their sensitive counterparts to baloxavir. No significant differences in baloxavir susceptibilities were found between the NA inhibitor-resistant and -sensitive viruses. We also examined representative seasonal influenza viruses isolated during the 2017–2018 influenza season in Japan and found that no currently circulating A(H1N1)pdm09, A(H3N2), or B viruses had significantly reduced susceptibility to baloxavir and none of the viruses possessed an amino acid substitution at PA residue 38. Use of a combination of methods to analyze antiviral susceptibility and detect amino acid substitutions is valuable for monitoring the emergence of baloxavir-resistant viruses.